2015
DOI: 10.1093/cid/civ235
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Risk of Endocarditis Using a Clinical Tool (PREDICT): Scoring System to Guide Use of Echocardiography in the Management of Staphylococcus aureus Bacteremia

Abstract: We propose 2 novel scoring systems to guide use of echocardiography in SAB cases. Larger prospective studies are needed to validate the classification performance of these scoring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 34 publications
5
108
3
2
Order By: Relevance
“…Infectious Diseases physicians most commonly cited a low suspicion for endocarditis due to rapid clearance of blood cultures as the reason for not pursuing TEE. Although it is well established that negative follow-up blood cultures are associated with a lower risk of endocarditis [1, 10, 11], TEE may identify subclinical endocarditis in a subset of these cases [5]. Despite this, our data suggest that when clinical and microbiological data are not indicative of endocarditis, ID physicians do not routinely feel compelled to pursue a diagnosis of subclinical endocarditis using TEE.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Infectious Diseases physicians most commonly cited a low suspicion for endocarditis due to rapid clearance of blood cultures as the reason for not pursuing TEE. Although it is well established that negative follow-up blood cultures are associated with a lower risk of endocarditis [1, 10, 11], TEE may identify subclinical endocarditis in a subset of these cases [5]. Despite this, our data suggest that when clinical and microbiological data are not indicative of endocarditis, ID physicians do not routinely feel compelled to pursue a diagnosis of subclinical endocarditis using TEE.…”
Section: Discussionmentioning
confidence: 70%
“…This may be appropriate because the standard of care for SAB is a minimum of 2 weeks of therapy [7], a treatment duration that has been shown to be effective even for established right-sided endocarditis [12, 13]. This practice is also consistent with a growing body of evidence that suggests TEE may not be necessary in cases of SAB with low-risk clinical features [1, 3, 10, 11, 14]. The recent update to the national guideline for the management of endocarditis acknowledged that “further work is needed to better define the subgroup of patients with bloodstream infection caused by S aureus who need only TTE to evaluate for infective endocarditis.” However, given the discordance between clinical practice and the recommendation to routinely perform TEE and the emerging evidence that TEE may not be necessary in all cases, this controversy should be more fully addressed in future guideline revisions.…”
Section: Discussionmentioning
confidence: 79%
“…Given the significant risk of IE with score ≥3 and the high sensitivity of transesophageal echocardiogram, the authors suggested transesophageal echocardiogram as the initial test for such high‐risk patients. Other simpler risk stratification models based on 3‐4 clinical risk factors have been validated by others and appear to perform equally well in identifying patients at low risk who might not need echocardiography and those at high risk who need early TTE, and possibly transesophageal echocardiogram, as the initial test …”
Section: Discussionmentioning
confidence: 99%
“…In SAB, the sensitivity of TTE is 24%–58% with a specificity of 99%–100% for the diagnosis of IE . The sensitivity of TTE is lower in patients with high‐risk clinical features including the presence of prosthetic valves, cardiac implantable electronic devices, community‐acquired SAB, intravenous drug use, and/or bacteremia persistent for >72 hours . Recent studies have identified, however, that in patients without high‐risk features, a normal TTE study has adequate sensitivity to rule out IE in SAB …”
Section: Discussionmentioning
confidence: 99%